Problem-Based Learning Learning Strategy at SMK Plus Al Hadi, Rengel District - fachrizal, nurul ivan; Hamim, Moh; Fathoni, Fathoni; Faizin, Mohamad (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2023)
Selection of the right learning method is necessary because it will greatly determine the ability of students in learning outcomes. In response to this problem, an appropriate learning model is needed, one of which is the PBL learning model. Formulation of the Problem (1) How is the application of the Problem-Based Learning learning model in PAI learning in Class XI of SMK Plus Al Hadi, Rengel District? (2) How to increase students’ critical thinking from the application of the Problem-Based Learning learning model in PAI learning in Class XI SMK Plus Al Hadi, Rengel District. This study aims (1) to describe the application of the Problem-Based Learning learning model to PAI learning in Class XI of SMK Plus Al Hadi, Rengel District. (2) To explain how to increase students’ critical thinking from the application of the problem-based learning model in PAI learning in Class XI SMK Plus Al Hadi, Rengel District. The analysis of this research data is qualitative and quantitative. Data collection techniques in this study include observation, tests, interviews and documentation. The results of this study were that the percentage of students who scored critical thinking skills met completeness in Cycle I was 65.62%, and in Cycle II it was 96.87%. The percentage of the number of students who met the completeness score in Cycle II had met the classical success indicators